Lipid metabolism reprogramming and its potential targets in cancer. Issue 1 (21st May 2018) - Cheng, Chunming; Geng, Feng; Cheng, Xiang; Guo, Deliang
Abstract: Reprogramming of lipid metabolism is a newly recognized hallmark of malignancy. Increased lipid uptake, storage and lipogenesis occur in a variety of cancers and contribute to rapid tumor growth. Lipids constitute the basic structure of membranes and also function as signaling molecules and energy sources. Sterol regulatory element‐binding proteins (SREBPs), a family of membrane‐bound transcription factors in the endoplasmic reticulum, play a central role in the regulation of lipid metabolism. Recent studies have revealed that SREBPs are highly up‐regulated in various cancers and promote tumor growth. SREBP cleavage‐activating protein is a key transporter in the trafficking and activation of SREBPs as well as a critical glucose sensor, thus linking glucose metabolism and de novo lipid synthesis. Targeting altered lipid metabolic pathways has become a promising anti‐cancer strategy. This review summarizes recent progress in our understanding of lipid metabolism regulation in malignancy, and highlights potential molecular targets and their inhibitors for cancer treatment.